2021
DOI: 10.1186/s12913-021-07382-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting utilization of sexual and reproductive health services among women with disabilities- a mixed-method cross-sectional study from Ilam district, Nepal

Abstract: Background Persons with disabilities can have physical, mental, intellectual, or sensory impairments which can hinder their social participation. Despite Sustainable Development Goals call for “universal access to sexual and reproductive health (SRH)”, women with disabilities (WwDs) continue to experience barriers to access SRH services in Nepal. This study evaluated factors affecting the utilization of SRH services among WwDs in Ilam district, Nepal. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…According to both male and female deaf persons, young deaf women are more likely to engage in abortion than girls because of the sexual edge among the youth. This finding is partly consistent with that of other studies on the greater exposure of young girls to poor SRH practices than older women [ 39 , 66 ]. Once again, culture and stereotypes in society could help explain this trend.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to both male and female deaf persons, young deaf women are more likely to engage in abortion than girls because of the sexual edge among the youth. This finding is partly consistent with that of other studies on the greater exposure of young girls to poor SRH practices than older women [ 39 , 66 ]. Once again, culture and stereotypes in society could help explain this trend.…”
Section: Discussionsupporting
confidence: 93%
“…It was revealed that participants who indicated that they were married were more likely to be knowledgeable about pregnancy and contraceptive methods than those who indicated that they were single. This finding partly substantiates that of another study regarding the high level of SRH knowledge among married compared to single persons [ 66 ]. Persons who are single and deaf do not have access to SRH because they engage less with these services, and policies do not generally target their needs.…”
Section: Discussionsupporting
confidence: 90%
“…As participants grow, they more likely would be unsatisfied with SRH services-a trend that is unexpected. Although previous study has reported the likelihood of aged persons with disability to utilize SRH services [38], this study has shown that they might not be satisfied with the service they were provided. The expectation is that the older the deaf persons, the more likely they would be to have experience, develop knowledge of SRH, and be able to support their dependents.…”
Section: Discussionmentioning
confidence: 63%
“…In low-or middle-income contexts, little attention has been given to the experiences of deaf persons [20-22, 26, 37] and persons with other disability conditions [37][38][39][40] in accessing SRH services. In a Nepalese mixed-method study, 384 persons with disability of reproductive age to understand factors affecting the utilization of SRH services [38]. The finding showed inaccessible health facilities and marital status impacted access to services.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that SRH services did not respond well in terms of the 6 A’s—approachability, acceptability, availability, accommodation, affordability, and appropriateness—reflecting the social dynamics [ 77 ]. Barriers can be classified as socioeconomic, structural, and attitudinal [ 79 , 84 ]. Socioeconomic barriers encompassed a lack of empowerment, a lack of family support, and cultural and religious factors.…”
Section: Resultsmentioning
confidence: 99%